DEVELOPING ENGLISH READING MATERIALS OF PROCEDURE TEXT BASED ON SCHEME BASE APPROACH IN SMK SWASTA ERIA MEDAN - Dayanur Dayanur; Sumarsih Sumarsih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
DEVELOPING ENGLISH READING MATERIALS OF PROCEDURE TEXT BASED ON SCHEME BASE APPROACH IN SMK SWASTA ERIA MEDAN *Dayanur ** Sumarsih ABSTRACT Dayanur. Registration Number: 2132121007. Developing English Reading Materials of Procedure Text based on Sheme base Approach in SMK Swasta Eria. A thesis. English Education Study Program, Medan State University, 2021. This study aimed to develop English reading material for students based on scheme base approach in vocational school. The study conducted by using Research and Development (R&D). The respondent of this research was 31 students of Office Administration grade XI in SMKS ERIA Medan. The data was consisted of syllabus, lesson plan, and existing reading materials. Based on the data, the existing reading materials were not appropriate for students of office administration department because those were intended for general students. The instruments of collecting data were questionnaires and interview to students and English teacher. This aimed to collect the data and information about students‟ needs and learning needs. The need analysis showed the needs of students on English reading materials. Based on the need analysis and material evaluation, the new reading materials were developed by associating to contextual teaching and learning approach, students‟ need and their department. The genre of text was procedure text which told about the manual steps. After designing the product, the experts validated the product. And finally, the English reading materials for office administration students could be used. The developed reading materials were how to use LCD projector in an office meeting, how to print a document, how to use a scanner, how to use a photocopier, and sending a fax. The product had been validated by an English lecturer and an English teacher with the mean score was 3,585 from 4. The product was categorized as “ Very Good and Relevant” reading materials for eleventh grade students of office administration program. Keywords: Reading Materials, Scheme Base Approach, Research and Development, Office Administration Program.